2012
DOI: 10.1021/ie300801e
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Voidage of Sinter Ores in the Tubes

Abstract: An industrial vertical tank (cost $200,000) was produced to recover the heat of sinter ores in our laboratory, the voidage along the height direction needs to be studied in order to determine the best height of sintering layer in it. In this paper, the bulk bed voidage of sinter ores in cylindrical polyvinylchloride tube (PVC-U) was measured by the cross-section image analysis method. The large-diameter tube was used to minimize the wall effects so that we could measure the bulk bed voidage in the center of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…D of the tube was 270 mm, which was comparable to those adopted by Zhang et al (2012) in their study to measure the packing voidage of SOPs.…”
Section: Packed Bed Test Setup and Proceduresmentioning
confidence: 55%
See 2 more Smart Citations
“…D of the tube was 270 mm, which was comparable to those adopted by Zhang et al (2012) in their study to measure the packing voidage of SOPs.…”
Section: Packed Bed Test Setup and Proceduresmentioning
confidence: 55%
“…The bed voidage for the unsorted case is almost identical to that for the size range of 30-40 mm, corresponding to an average equivalent particle diameter of 18.60 mm. Note that the bed voidage in this study is greater than the value of about 0.4 reported by Zhang et al (2012), although packed beds with comparable diameter and height and SOPs with similar sizes were adopted. The irregular shape of the SOPs is confirmed by the measured sphericity ranging from 0.62 to 0.66.…”
Section: Geometric Properties Of the Sopsmentioning
confidence: 63%
See 1 more Smart Citation
“…During the packing process, the iron ore granules at the lower part appeared certain of tamping caused by adhering layer deformation under the weight of granules above, 26) then fine granules in the upper part of the packed bed would fall down to occupy the voids in the lower part, which led to the denser packing at the lower part of the packed bed. 27,28) The porosity at the top and bottom of the packed bed exhibits a significant increase, which can be explained by wall effect, namely influenced by top and bottom wall of the container. Both topmost and bottommost granules of the packed bed were forced to form neatly arranged layers along the walls of top and bottom, and due to the point contact of granules with container wall, the porosity at the wall is higher than the other part of packed bed.…”
Section: Porosity Distribution Of Granule Packed Bedmentioning
confidence: 99%
“…This finding agrees with the results observed from the S/N ratio analysis in Section 3.3. Studies have shown that the porosity fluctuation along packed bed height increases as the tube to granule diameter ratio decreases, 27) thus for a given container diameter, the larger granule size is, the greater axial porosity fluctuates. It can be concluded from the foregoing discussion that moisture is the dominant factor affecting granule size, and therefore contributes most to axial porosity segregation.…”
Section: Anova Analysismentioning
confidence: 99%